1997
DOI: 10.1097/00005537-199703000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Swallowing Safety With Fiberoptic Endoscope: Comparison With Videofluoroscopic Technique

Abstract: Videofluoroscopy has long been viewed as the "gold standard" of swallowing examination for the comprehensive information it provides. However, it is not very efficient and accessible in some practical situations. In this study, we tried to use a modified technique of fiberoptic endoscopic examination of swallowing (FEES) in evaluating dysphagic patients. For each examination, a spoonful of pudding and dyed water were fed in sequence three times. The pharyngeal swallowing events were observed with fiberscope pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(31 citation statements)
references
References 13 publications
2
27
0
Order By: Relevance
“…When doing this, it is possible (albeit rare) to encounter adverse events. These may include side effects such as discomfort, gagging and/or vomiting, and complications such as anterior epistaxis, posterior epistaxis, laceration of the mucosa, allergic reactions/hypersensitivity to topical anaesthesia or nasal spray, adverse reactions to methylene blue (contraindicated in favism), vasovagal response and laryngospasm [1,16,31,32,33,34,35]. Discomfort has been referred to as the most frequently reported adverse event; the use of topical anaesthesia may reduce the occurrence of this, though it may alter the swallowing mechanisms [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When doing this, it is possible (albeit rare) to encounter adverse events. These may include side effects such as discomfort, gagging and/or vomiting, and complications such as anterior epistaxis, posterior epistaxis, laceration of the mucosa, allergic reactions/hypersensitivity to topical anaesthesia or nasal spray, adverse reactions to methylene blue (contraindicated in favism), vasovagal response and laryngospasm [1,16,31,32,33,34,35]. Discomfort has been referred to as the most frequently reported adverse event; the use of topical anaesthesia may reduce the occurrence of this, though it may alter the swallowing mechanisms [33].…”
Section: Discussionmentioning
confidence: 99%
“…For several years now, and especially in the latest reports in the literature, it has been demonstrated that FEES can be better at determining penetration, aspiration and residue, therefore these two investigations should be considered complementary rather than competitors [12,16]. Other tests that are considered complementary for studying dysphagia are oro-pharyngo-oesophageal scintigraphy [17,18,19], ultrasound [20,21,22,23], pH manometry [24,25,26,27] and, most recently, high-resolution manometry [27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fiberoptic endoscopic evaluation of swallowing (FEES), on the other hand, is generally well tolerated and therefore frequently repeatable [20]. FEES can be performed at the bedside like a usual clinical examination, and has a similar sensitivity and specificity for detecting signs of dysphagia, especially silent aspiration, to videofluoroscopy [21,22,23,24]. Reports indicate that FEES has the potential to significantly improve regular swallowing assessment in acute stroke care [25].…”
Section: Introductionmentioning
confidence: 99%
“…With the improvement presented by the patient and with good results observed in such a short period of time, the medical team believed that the performance of an objective test for swallowing would be advantageous (Ott, 1998;Chih Hsiu et al, 1997;Hinds & Willes, 1998;Ertekin & Aydogdu, 2003) in order to prove the absence of any kind of alteration during swallowing. With this, new procedures could be established in order to guarantee success, given the rapid improvement.…”
Section: Discussionmentioning
confidence: 99%